A Study of Job Stress Among Professional Accountants Working in Selected Public Accounting Firms : A Malaysian Case (Malaysian Management Journal, 1992)
The study replicates and extends earlier studies on job stress in public accounting conducted in the United States (Gaertner and Ruhe, 1981) and Britain (Lyall, 1984) it is done through an extensive review of literature on job stress and field study using the same questionnaire as utilized in the two earlier studies with only slight modifications are made to suit the Malaysian context. The study seeks answer to what may be the sources of stress, psychological outcomes and moderators of stressful situations in selected public accounting firms and whether there exist significant linear relationships between the job stressors and mental strains. Furthermore, it attempts to find out whether different firm sizes, functional areas and position levels differ significantly in the stressors confronted and strains experienced by the public accountants. The findings indicate that stressors faced by most respondents are quantitative workload, variations in workload, responsibility for persons and travel. Very few report confronting role conflict and role ambiquity. As for the mental strains, respondents do not show that they are experiencing any except for job and workload dissatisfactions and pa inequity. It is also found that more than 70 percent of the respondents feel that they have job autonomy and that they do not possess the Type A personality traits.